Analisis Dampak Penggunaan Media Sosial Terhadap Sikap, Perilaku, dan Karakter Siswa SD - Rachmawati S, Aulia Intan; Ratnaningrum, Ika (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In this modern era, of course our lives cannot be separated from technology and social media. The Covid-19 pandemic has also had a major influence on the increase in social media use. At the elementary school (SD) level, children are certainly familiar with social media. Various platforms such as YouTube, Instagram, Tiktok, and so on make it easy for elementary students to access various learning materials. Apart from learning materials, students can also access various content and information globally. This easy access certainly makes students impacted by what they have seen and been involved in, both positive and negative. In this research, the author will explain the analysis of the impact of using social media on the attitudes, behavior and character of elementary school students using qualitative methods with literature studies. Through this research, the author hopes to provide a deeper understanding of the implications of children's interactions with social media, as well as how this affects their development at the elementary school level.